HUBUNGAN MEDIA VIDEO TUTORIAL DAN MINAT BELAJAR TERHADAP HASIL BELAJAR SISWA MAPEL GAMBAR TEKNIK DI SMKN 1 KEMLAGI - Satriya Utama; Ninik Wahju Hidajati (Jurnal Kajian Pendidikan Teknik Bangunan, 2023)
The results of the observations carried out in the State Department of 1 Kemlagi showed that there areproblems that show that the practical equipment of the engineering subjects painting is considered to beinadequate and not functioning optimally. Based on this, the study is based on the aim of finding out therelationship between the learning medium (X1) and the student's learning interest (X2) in the learningoutcomes of students (Y) in class X on engineering drawing subjects. This research uses quantitativeresearch methods of the correlational type. Data collection techniques were used in this research toobtain information about the development of learning media, such as interviews, lifts, and posttests. Theresults of the study revealed that there was a positive and significant relationship between the learningmedia and the learning outcomes of students with strongly categorized students seen from the results ofpearson correlation gaining a score of 0.631 and the significance value (2-tailed) of 0.0095<0,05, founda positively and significant relation between the student's learning interests with the learning results ofstudents of strong categories seen from Pearson's correlations gaining the value of 0.651 and significance(-2-tailing) of 0,0064<0,05 and found a positive, significant relationship among the learning medium andstudent interest with the student learning outcome of strongly classified students seen of the result of theCorrelation coefficients X1 and X2 versus Y of 0.066 and the test result of F of 0,000<05.